Understanding Human Right Based Education in Early Childhood Education - Husnah, Ziadatul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study focuses on the design of human rights-based learning model in early childhoodeducation. There are two important academic problems in this study. Firstly, why is it necessarily needed for early childhood education to develop human rights-based learning model in the classroom? Secondly, what is the most appropriate learning model to habituate human rights values in the classroom? By employing interpretive paradigm this study concluded that early childhood education needed to develop human rights-based learning model in the classroom because philosopically this model is compatible with and to reaffirm the essence of education that every learning process should respect the uniqueness of students’ potential, protect them from negative treatments and deeds such as discrimination and bullying, dan fulfill universal needs of students namely loved, undesrstood, valued, respected, and safe. Besides, teachers in early childhood education as one of duty bearers have to design human rights values-based learning in their classroom either in the lights of class setting, learning model, learning strategies and teacher himself as human rights living model